Effect of polymer molecular weight and processing solvent on the morphology and photovoltaic performance of inverted non-fullerene solar cells. (October 2021) - Zheng, Xinming; Lu, Hao; Feng, Shiyu; Hou, Ran; Liu, Wenlong; Ming, Shouli; Xu, Xinjun; Wu, Youzhi; Bo, Zhishan
Abstract: Nonfullerene acceptors (NFAs) usually exhibit narrower bandgaps and stronger aggregation than fullerene derivatives, so donor polymers compatible with NFAs to achieve high-performance photoelectric conversion are presently limited to only several popular examples. To boost the device efficiency without changing the molecular structure of the material, we investigate the influence of polymer's molecular weights on the photovoltaic performance of polymer solar cells (PSCs). It was found that the molecular weight of a typical donor polymer (PBDB-T) can significantly impact on the film microstructure, charge transport and device performance of NFA based PSCs. Moreover, we find that changing the processing solvent exerts various impacts on the trend of the influence of molecular weight upon the performance of the device. Polymers with both a high and a low molecular weight can demonstrate a comparable photoelectric conversion efficiency, depending on what kind of processing solvent is used. It is concluded that in order to obtain a better morphology, charge carrier mobility and high device efficiency, polymers with a high molecular weight prefer to choose a solvent with a better solubility, while the ones with a low molecular weight would rather use a solvent with a weaker solubility. Highlights: The influence of polymer molecular weight on the photovoltaic performance of polymer solar cells (PSCs) is investigated. The molecular weight of a donor polymer can significantly impact on the film microstructure and charge transport in PSCs. Polymers with both a high and a low molecular weight can demonstrate a comparable photoelectric conversion efficiency.